If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x(x + -2) + -4 = (x + -4) + 6 Reorder the terms: x(-2 + x) + -4 = (x + -4) + 6 (-2 * x + x * x) + -4 = (x + -4) + 6 (-2x + x2) + -4 = (x + -4) + 6 Reorder the terms: -4 + -2x + x2 = (x + -4) + 6 Reorder the terms: -4 + -2x + x2 = (-4 + x) + 6 Remove parenthesis around (-4 + x) -4 + -2x + x2 = -4 + x + 6 Reorder the terms: -4 + -2x + x2 = -4 + 6 + x Combine like terms: -4 + 6 = 2 -4 + -2x + x2 = 2 + x Solving -4 + -2x + x2 = 2 + x Solving for variable 'x'. Reorder the terms: -4 + -2 + -2x + -1x + x2 = 2 + x + -2 + -1x Combine like terms: -4 + -2 = -6 -6 + -2x + -1x + x2 = 2 + x + -2 + -1x Combine like terms: -2x + -1x = -3x -6 + -3x + x2 = 2 + x + -2 + -1x Reorder the terms: -6 + -3x + x2 = 2 + -2 + x + -1x Combine like terms: 2 + -2 = 0 -6 + -3x + x2 = 0 + x + -1x -6 + -3x + x2 = x + -1x Combine like terms: x + -1x = 0 -6 + -3x + x2 = 0 Begin completing the square. Move the constant term to the right: Add '6' to each side of the equation. -6 + -3x + 6 + x2 = 0 + 6 Reorder the terms: -6 + 6 + -3x + x2 = 0 + 6 Combine like terms: -6 + 6 = 0 0 + -3x + x2 = 0 + 6 -3x + x2 = 0 + 6 Combine like terms: 0 + 6 = 6 -3x + x2 = 6 The x term is -3x. Take half its coefficient (-1.5). Square it (2.25) and add it to both sides. Add '2.25' to each side of the equation. -3x + 2.25 + x2 = 6 + 2.25 Reorder the terms: 2.25 + -3x + x2 = 6 + 2.25 Combine like terms: 6 + 2.25 = 8.25 2.25 + -3x + x2 = 8.25 Factor a perfect square on the left side: (x + -1.5)(x + -1.5) = 8.25 Calculate the square root of the right side: 2.872281323 Break this problem into two subproblems by setting (x + -1.5) equal to 2.872281323 and -2.872281323.Subproblem 1
x + -1.5 = 2.872281323 Simplifying x + -1.5 = 2.872281323 Reorder the terms: -1.5 + x = 2.872281323 Solving -1.5 + x = 2.872281323 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '1.5' to each side of the equation. -1.5 + 1.5 + x = 2.872281323 + 1.5 Combine like terms: -1.5 + 1.5 = 0.0 0.0 + x = 2.872281323 + 1.5 x = 2.872281323 + 1.5 Combine like terms: 2.872281323 + 1.5 = 4.372281323 x = 4.372281323 Simplifying x = 4.372281323Subproblem 2
x + -1.5 = -2.872281323 Simplifying x + -1.5 = -2.872281323 Reorder the terms: -1.5 + x = -2.872281323 Solving -1.5 + x = -2.872281323 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '1.5' to each side of the equation. -1.5 + 1.5 + x = -2.872281323 + 1.5 Combine like terms: -1.5 + 1.5 = 0.0 0.0 + x = -2.872281323 + 1.5 x = -2.872281323 + 1.5 Combine like terms: -2.872281323 + 1.5 = -1.372281323 x = -1.372281323 Simplifying x = -1.372281323Solution
The solution to the problem is based on the solutions from the subproblems. x = {4.372281323, -1.372281323}
| 12/10=y/5 | | 35w=145 | | 36/8=9/k | | -2(3-2x)=5+3(2x-4) | | 17+2c=16 | | 0.5x^3-3x=0 | | c+12=42 | | -1,5x+1000=-2x+2500 | | 3y+7=62 | | 7r/8+7r/12=5r-10/3 | | 2p-4=8 | | 4x+500=1,5x+225 | | 2x-4(2x+1)=x-3(2x-1) | | 5x+9y=-8 | | 28x-8(4x+3)=3(2x-3) | | 28-8(4x+3)=3(2x-3) | | -81=7k+9+3k | | 81=9x+5 | | 70=203-19x | | 70x=203x-19 | | x/9-(1+2x)=19-2x | | 2X-5=25WHATISX | | 19x=70x-19 | | 4(6+8s)-(2s+1)=60s+8 | | 19=70x-19 | | 31-9x=1-3(4x-17) | | 19=70x-2 | | 117x=17x+6 | | 117=17x+6 | | 27x=1 | | 19=40x+5 | | 117=40x+7 |